Village Government Strategies For Sustainable Management Of Village Funds In Minta Kasih Village, Langkat Regency - Sri Wahyuningsih; Vina Arnita (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This study aims to analyze the government's strategy in Minta Kasih Village, Langkat Regency, in managing Village Funds sustainably. Village Fund management has tended to focus on physical development and administrative reporting, but has not fully considered social and environmental sustainability. This study used a qualitative narrative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The results indicate that the Village Fund planning and implementation strategy has been carried out in accordance with regulations and is based on deliberation. Programs implemented include the construction of drilled wells, alleyways, Family Empowerment and Welfare (PKK) activities, and training for village officials. However, community participation is still limited, village social institutions are not optimal, and environmental aspects have not been prioritized in village planning. Program evaluation also still focuses on administrative reporting, rather than on long-term impacts. To address these challenges, this study recommends five strategies: establishing a hamlet community forum, strengthening social institutions, implementing a household waste management program, utilizing land for educational green spaces, and developing digital village information media. By strengthening these strategies, it is hoped that Village Fund management can have a greater social, ecological, and sustainable impact. In addition, this study contributes theoretically by highlighting the importance of integrating participatory governance and environmental sustainability into rural development policies. Practically, it provides a reference for policymakers, village governments, and community organizations in formulating inclusive, transparent, and environmentally conscious strategies for Village Fund management. The findings also emphasize the need for continuous capacity building for village officials and increased awareness among communities to ensure that the Village Fund not only fulfills regulatory compliance but also creates long-term benefits for future generations.